Effect of Mercury Concentration and Operating Parameters on Mercury Removal Using Portable Mercury Removal Rig for Petrochemical Wastewater - Sulaiman, Z.; Azoddein, A.A.M.; Sayuti, S.C. (Journal of Engineering and Technology (JET), 2015)
Mercury is a type of heavy metal that naturally occurs in the earth’s crust, which can be found in soil, rocks and sea. Mercury is released to the environment through natural processes such as rock erosion, soil decomposition or volcanic eruptions and also released through human activities, petrochemical industrial processes and chlor-alkali industries. Mercury is widely used in the thermometer, thermostat, barometer, bulbs, dental amalgams and switches. Other than that, mercury is one of the hazardous chemical elements that exist on the earth that can attack the human central nervous system, kidney, lungs and other body systems. Portable Mercury Removal Rig (PMRR) was used in mercury removal process under room temperature with different operating pressure; 5, 10 and 23 psig, different inlet concentration; 2, 4, 6 and 8 ppm, different pH and by using different absorbent; extruded activated carbon (EAC), granular activated carbon (GAC) and ion exchange (IE) resins. Extruded Activated Carbon (EAC) was the best absorbent with pH sample range from 2 to 4 in using the PMRR. It was also found that 5 psig was the best operating pressure and concentration from 2 to 4 ppm was the most suitable concentration to be used. This study shows that EAC can be used as an efficient absorbent in removing mercury in wastewater as it give about 99.8 % of mercury removal.